Fractional order PID controller design for wind turbine systems using analytical and computational tuning approaches. (October 2021) - Frikh, Mohamed Lamine; Soltani, Fatma; Bensiali, Nadia; Boutasseta, Nadir; Fergani, Nadir
Highlights: A recently proposed analytical fractional order PID controller design approach is applied to control the speed of a two-mass wind turbine system. The wind turbine complex nonlinear system is commonly modeled as a two-mass system because of its inherent advantages. The fractional order controller design technique allows the design of the Fractional order PID parameters according to desired specifications terms of phase margin and unity gain crossover frequency. The closed loop system behaves as Bode's ideal transfer function, the iso-damping propriety is verified. Good precision both in phase margin and unity gain crossover frequency is obtained for wide variety of linear systems. Simulation results show the higher performance of the applied technique when compared with computational tuning approaches in terms of multiple performance evaluation indices. Abstract: In this paper, a recently proposed analytical fractional order PID controller design approach is applied to control the speed of a two-mass wind turbine system. The wind turbine complex nonlinear system is commonly modeled as a two-mass system because of its inherent advantages. On the other hand, wind turbulence and high overshoot are factors that cause stress in wind turbines which may be alleviated using an adequate speed control strategy. The applied technique allows the design of the fractional order PID parameters according to desired specifications in terms of phase margin and unity gain crossover frequency. The main advantage of using such tuning method is that the closed loop system behaves as Bode's ideal transfer function. Simulation results show the higher performance of the fractional order PID controller design technique when compared with computational tuning approaches in terms of multiple performance evaluation indices. Graphical abstract: Image, graphical abstract